The vitamins - Combs, Gerald F; Jr (Elsevier/Academic Press, 2012)
"The fourth edition of this bestselling book continues to provide the latest coverage of the biochemistry and physiology of vitamins and vitamin-like substances. Cross-cutting, health-related themes present insights into the use of vitamins not just for general nutritional balance, but with emphasis on their roles in the prevention and/or treatment of specific health issues such as inflammatory diseases, overweight and immune function. Information is presented to address the roles of vitamins in gene expression and epigenetics, providing important information in the further development of personalized medical treatments and establishing appropriate dietary programs based on individual genetic profiles. Those working in nutrigenomic and pharmaceutical developments will use the information to identify potential benefits of vitamins alone or in combination."--Page 4 of cover.